Castoriadis and Cognitive Linguistics: A Research Trajectory in the Form of 12 Busy Fragments - Hastings-King, Stephen (Nordicum-Mediterraneum, 2008)
If there is a problem with Castoriadis' work, it is that few know about it. In the United States, any number of factors may explain the superficiality of reception, from the way in which Castoriadis’ work moves across genres to the institutional configuration that has monopolized "French Theory" to the radical consequences entailed by his work for existing modes of information definition and organization.